REDUCING OCCUPATIONAL RISK IN INDUSTRY BASED ON THE LABOR WEIGHT FACTOR - Rakhimov Oktyabr Dustkabilovich; Tulayeva Sokhiba Akbar kizi (Bright Mind Publishing, 2025)
The article presents the theory of risk and its role in ensuring occupational safety, the methodology for quantitative assessment of possible accidents, methods for determining risk. The concept of acceptable, permissible risk, the theory of risk management, and methods for preliminary analysis of risks are discussed.
Keywords: Theory, risk, quantitative assessment, concept, acceptable, methods, model, engineering, expert, social, survey.